“It takes a village to raise a child,” university teachers’ views on traditional education, modern education, and future I integration in Ethiopia - Baheretibeb, Yonas; Whitehead, Cynthia (Frontiers in Education, 2024)
Indigenous education has recently gained prominence in international debates for its role in addressing the social, economic, and political issues faced by African states. Ethiopia, like other African countries, had its education system based primarily on the transmission of socio-professional aptitudes, religious values, skills, and intergenerational knowledge as a way to preserve the social, cultural, and religious values of the Ethiopian community. In the early 20th century, Ethiopia wholeheartedly adopted a Western higher education system in a tabula rasa approach that sought to obliterate deeply rooted cultural norms and rapidly transition the country's traditional religious system to a secular one. This qualitative study used semi-structured interviews to explore the perspectives of Ethiopian university teachers about the benefits and limitations of traditional education and the potential to integrate traditional and modern education in Ethiopian universities. Study findings show that, despite agreement that "traditional" education is distinct from other educational systems, there are varying notions of what constitutes "indigenous" education. Participants also suggested that the dominant rationale for the tabula rasa approach in Ethiopian modern education was to modernise the country and embrace a global perspective on education that incorporates ideas and advances from other cultures while still being firmly entrenched in local values and educational systems. These insights have implications for education systems in African and other low-and middle-income countries (LMICs) in terms of developing strategies for the pluralistic approach to knowledge systems.